Prevalence of Candida Albicans in Genital Tract of Pregnant Women Attending Antenatal Clinic of Nepalgunj Medical College Hospital - Rai, Maya; Poudel, T. P.; Gurung, K.; Neupane, G. P.; B.C., Durga (Journal of Nepalgunj Medical College, 2017)
Introduction: Pregnancy is one of the important risk factor for occurrence of vaginal candidiasis which may lead to pregnancy complications like abortions, premature birth, low birth weight and other morbidities. It is essential to know pattern of distribution of the species of Candida that are pathogenic. Aim and Objective: To identify prevalence of Candida albicans in the genital tract of pregnant women. Materials and Methods: Total of 100 vaginal swabs were collected from 100 pregnant women attending at antenatal clinic of Gynaecology and Obstetrics department for a period of six months from March 2017 to August 2017. Gram's staining and inoculation onto Sabouraud dextrose agar (SDA) medium were done for general identification of yeast and to isolate the positive cases. The specifications of Candida species was done on the basis of sugar fermentation, carbohydrate assimilation, production of germ tube in fresh human serum, formation of chlamydospore on Cornmeal agar and colour of colony on CHRO Magar. Results: Out of 100 high vaginal swabs 40(40%) samples were positive for Candida. Of these positive samples, Candida albicans was isolated in 52.5% of pregnant women. Candida albicans was most commonly isolated in the age group of 25-29(38.09%), in third trimester of pregnancy and in the multigravidae. Conclusions: High prevalence of Candida albicans species among pregnant women were documented in this study. Our results indicate that gravidity, as the risk factor for occurrence of infection, has the significant role in the occurrence of vaginal candidiasis.